Las danzas de salón tango y samba en las ciudades de Buenos Aires, Montevideo y San Pablo, desde una perspectiva de género - Jose Manuel Alvarez Seara (2021)
This thesis has been proposed to investigate, from a gender and sexual di- versity perspective, gender stereotypes, heteronormativity and barriers in tango and samba ballroom dances, considered as leisure practices. It seeks to identify what are the resistances and strategies that practitioners linked to the LGBTI and Queer community and teachers propose in order to face and overcome these barriers in order to have a satisfactory leisure experience in these dances. This is a qualitative, exploratory research work in three Latin American cities: Buenos Aires (Argentina), Montevideo (Uruguay) and San Pablo (Brazil), were made semi-structured interviews were carried out with professors who are related and working in these dances from a perspective LGBT/Queer/Gay/Free. Were also made participant observations of classes and dances in which there have been participating people who are linked to the groups and/or perspective LGBT/Queer/Gay/Free and people that are not linked to these groups and/or perspective. The results confirm that the existence of barriers derived from gender ste- reotypes, product of heteronormative patterns, hinders not only the access and participation of people from LGBT/Queer/Gay groups and women in this type of dance, but also from its enjoyment as a leisure practice. However, the affected people react to the barriers and look for negotiation strategies with them, in order to avoid them, eliminate them or mitigate their effects.